THE CONSUMPTION OF MEAT IN BRAZIL: BETWEEN SOCIO-CULTURAL AND NUTRITIONAL VALUES - Cilene da Silva Gomes Ribeiro; Mariana Corção (Universidade do Estado do Rio de Janeiro, 2013)
This paper aims to address the two main spheres of valuation of meat consumption in Brazil: on one hand, the socio-historical aspects and, on the other, the nutritional aspects. To this end, the authors understand the symbolic food bias and consider the relevance of historical experience in the consolidation of eating habits. This paper begins in the context of colonial Brazil, with the inclusion of discursive values related to the consumption of meat. It presents characteristics of meat consumption in Brazil, intensified with the urbanization process from the 19th century. The nutritional speech is noteworthy, developed from the 1930s in Brazil, which ensured the idea of meat as food par excellence, dividing Brazil between those who have access to that food and those who do not. It highlights the importance of meat in the Brazilian food culture, represented especially in steakhouses. It also considers the demonstrations against the consumption of meat permeated by different ideological, ethical, aesthetic and ecological spheres. It intends, therefore, to crisscross lines of these different approaches, emphasizing the different symbolisms that cover the increased meat consumption in Brazil.